Principals' Role of Visionary Leadership Based on Ethical Culture in Improving School Quality: A Systematic Literature Review - Latif, M. Baihaqi Rizki Abdul; Sunandar, Asep; Juharyanto, Juharyanto (Yayasan Keluarga Guru Mandiri, 2026)
This research aims to investigate the role of school principals' visionary leadership based on an ethical culture in improving school quality. This research uses a systematic literature review method to examine several related articles. The research results show that visionary leadership by school principals plays a significant role and positively influences the quality of schools and institutions. The role of the school principal's visionary leadership style in improving the quality of education is demonstrated by several factors and characteristics of this style. The relationship between visionary leadership and ethical culture can drive innovation to improve the quality of education. The ethical culture in schools enables the formulation of the school's vision, mission, and goals by examining the school's characteristics and the community that participates in it. The final results of this research concluded that school principals who have vision, characteristics, competence, motivation, strong work standards, and a value orientation are leaders expected to improve the quality of education. This research is hoped to provide insight to other researchers, educators, school principals, and schools.